Improving the mental health system for trauma victims in France. Issue 1 (1st January 2019) - El-Hage, Wissam; Birmes, Philippe; Jehel, Louis; Ferreri, Florian; Benoit, Michel; Vidailhet, Pierre; Prieto, Nathalie; François, Irène; Baubet, Thierry; Vaiva, Guillaume
ABSTRACT: France has a rich history of exposure to large-scale traumas such as wars, disasters and terrorist attacks, and psychiatric teams specialized in emergency interventions for mass trauma have been created across the territory. However, no public resources are dedicated for long-term interventions or for individual trauma cases. This letter describes how a government supported model of care has been created and implemented in 2019. A national centre for resources and resilience (CN2R) and 10 regional ambulatory services specializing in psychotraumatology were created with the aim of improving public mental health-care delivery while providing a comprehensive suite of services for trauma victims from the most immediate to longer-term considerations.